KEEFEKTIFAN METODE STRUKTUR ANALISIS SINTESIS (SAS) DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SD NEGERI BALLEWE KABUPATEN BARRU - Jumriati Jumriati; Abu Bakar Tumpu (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2019)
Abstract: The Effectiveness of the Synthesis Analysis Structure (SAS) Method in Improving the Initial Reading Ability of Students Grade 1 at Ballewe Elementary School Barru Regency. This research aimed to determine the effectiveness of the synthesis analysis structure (SAS) method in improving the initial reading ability of students’ grade 1 at Ballewe elementary school Barru regency. The approach used in this research was quantitative approach with experimental methods. The population in this study was all students in grade 1 elementary school in Barru, consisted of 27 students. The instrument used to obtain data in this study was test instrument. Test technique was preliminary reading test. The results of this research indicated the paired sample test table sig (2.tailed), obtained a value of 0,000. The obtained value was smaller than the significance level of 0.05 which indicated that there was a significant difference in the 0.05 probability of students’ grade 1 learning outcomes. This showed that the application of the SAS method had an influence in improving initial reading skill.Keywords: synthesis analysis structure, Initial Reading.